ACADEMIC STRESS AMONG STUDENTS: A PERSPECTIVE OF MINDSET AND ACADEMIC HARDINESS - Analya, Priska; Adelina, Ira; Fun, Lie Fun; Lee, Andrew; Wijaya, Joanna (JURNAL EDUSCIENCE, 2025)
Purpose – Building on mindset theory (growth and fixed mindsets), which emphasizes beliefs about the malleability of ability, and the concept of academic hardiness (commitment, control, challenge) as a source of resilience in coping with academic pressure, this study examines the roles of both factors in university students' academic stress. Prior research has more often tested mindset or hardiness separately, leaving the extent of their simultaneous contributions to predicting academic stress unclear, particularly in student populations. Hence, the present study is designed to examine the effect of mindset and academic hardiness on the students' view of academic stress.Methodology – This study employed a quantitative correlation design using convenience sampling, involving 468 undergraduate students in the city of Bandung. The data were analyzed using multiple regression and collected through the Mindset Scale, the Revised Academic Hardiness Scale (RAHS), and the Academic Stress Inventories.Findings – Academic hardiness was a significant and negative predictor of academic stress, whereas mindset was not a significant predictor of academic stress. The model accounted for 13.8% of the variance for academic stress, indicating that students' stress is more effectively buffered by resilience-related factors than by the cognitive orientation to stress.Contribution – The findings underscore academic hardiness as a stronger protective factor for managing academic stress. Practically, universities may prioritize strengthening hardiness through stress-management training, challenge-based learning, and support for emotion regulation to promote students’ adaptation and mental health.